Paleoenvironmental evolution of the southern Neuquèn basin (Argentina) during the Tithonian-Berriasian (Vaca Muerta and Picún Leufú Formations): a multi-proxy approach - Krim Nesma; Bonnel Cédric; Tribovillard Nicolas; Imbert Patrice; Aubourg Charles; Riboulleau Armelle; Bout-Roumazeilles Viviane; Hoareau Guilhem; Fasentieux Bertrand (BSGF - Earth Sciences Bulletin, 2017)
The Tithonian-Berriasian interval in the southern part of the Neuquén Basin is represented by the Vaca Muerta and the Picún Leufú Formations. Facies analysis and correlation of the Vaca Muerta Formation and the lower part of the Picún Leufú Formation in the Picún Leufú Anticline allow us to characterize the evolution of successive facies belts representing siliciclastic shelf and mixed ramp environments. Shoreface and offshore facies are developed on the siliciclastic shelf in the western and southern parts of the Picún Leufú Anticline. The offshore transition domain is characterized by storm beds and slump features, whereas the offshore domain corresponds to black to grey shales and turbidites. The mixed siliciclastic-carbonate ramp is characterized by the development of a lagoon and high-energy shoal in the proximal part of the inner ramp, whereas the distal part comprises a tidal complex. The mid-ramp zone is characterized by storm influence and the outer ramp by fine-grained deposits. Two major transgressive-regressive sequences and five high-frequency transgressive-regressive sequences are recognized. The high-frequency transgressive-regressive sequences make up three progradational sequences, an aggradational-progradational sequence and an aggradational sequence. The geochemical characteristics and clay mineralogy of the Tithonian-Berriasian interval in the southern Neuquén Basin indicate that (1) climate played a key role in the evolution of the sedimentary environment, (2) a “normal marine” depositional environment with oxic sea water and sediment pore waters, rapidly changing to suboxic conditions at shallow depth below the seabed and (3) the occurrence of episodically restricted water-mass circulation at the onset of deposition of the Vaca Muerta Formation.